3D numerical analysis of column shortening and shore safety under construction of high-rise building. (1st November 2017) - Lee, Yun; Kim, Jin-Keun; Seol, Hyun-Cheol; Yang, Joo-Kyoung; Kim, Ki-Jung
Highlights: A new method to examine column shortening and shore safety of high-rise building is developed. Both the construction sequence and the inelastic behavior of concrete are considered. Analysis results generally simulated the experimental data well in all cases. The effects of the construction method on column shortening and shore safety factors were examined. Abstract: An analysis method to examine the column shortening and shore safety of high-rise buildings from the construction period through the service life is developed. The effects of both the construction sequence and the inelastic behavior of concrete are considered in the analysis in three dimensions. The examination of safety during construction and the column shortening predictions are also discussed. Through a comparison of the analysis results and the measured data, it was found that the analysis results generally simulated the trends in the measured data well in all cases. Finally, the effects of the construction method on column shortening and shore safety were examined.